Pseudopolarography coupled with logarithmic additions for the determination of dissolved natural organic matter complexing properties toward copper - Louis, Y.; Omanovic, D.; Pizeta, I.; Mounier, S. (2007)
Complexation of trace metals in natural waters by natural organic matter and inorganic ligands i.e. their chemical speciation, determines their mobility and bioavailability. NOM is ubiquitous in the environment and consists of a complex mixture [1]. It is known to play important roles in the fate of many contaminants due to its complexing properties. A better determination of NOM structural and functional properties can greatly improve our understanding of the underlying mechanisms responsible for heavy metals complexation. Among the techniques allowing trace metals speciation in natural waters, voltammetry is really appropriate because it offers high sensitivity, enough selectivity and ability for direct measurement with minimal disturbance of the original sample. Obtained voltammetric data are related to the physico-chemical characteristics of the electroactive metal species, and information on speciation parameters of the investigated metal could be obtained. In this study, the ability of pseudopolarographic approach to trace metal speciation is investigated [2, 3]. Pseudopolarogram represents a series of anodic stripping voltammetric (ASV) peak current values plotted as a function of deposition potential. As in classical polarography, the parameters extracted from the pseudopolarograms are half-wave potential and limiting current. The reduction half-wave potentials of inert metal complexes are separated from the reduction potential of free and labile metal complexes and are shifted towards more negative values. The amount of these shifts is the basis for the determination of the type of inert metal complexes in natural waters, because they depend on their stability constant [4]. Pseudopolarography is used here, in addition of logarithmic additions of copper, to optimise a choice of accumulation/deposition potential where only free/labile metal is reduced which is a prerequisite for the procedure of metal complexing capacity (MCC) determination. The influence of accumulation potential on determination of metal complexing capacity was investigated, as well. Copper additions were performed in a logarithmic mode, allowing a wider analytical window, and therefore a better accuracy of the complexing parameters determination [5]. The voltammetric data were further modelled with PROSECE (Programme d’Optimisation et de SpEciation Chimique dans l’Environnement), a very manageable software based on a discrete model [5]. Calculated metal complexing parameters (ligand concentrations and stability constants) strongly depend on accumulation potential as well as on experimental setup, which needs to be better understood and quantified.